Gestational diabetes [ origins, complications and treatment - Petry, Clive J. (CRC Press, 2014)
"Discussing the origins, care, and consequences of gestational diabetes mellitus (GDM), this book focuses on evidence-based medicine to highlight various aspects of this rapidly growing condition. It provides glucose requirements for fetal growth and maternal and fetal metabolism as well as insulin secretion and sensitivity in pregnancy; covers genetic risk factors, autoimmunity, interaction with obesity, and associations with fetal growth genes; presents diet therapies and the role of exercise and nutrition; and reviews the effects of rapid-, short-, and long-acting insulin, oral hypoglycemic agents in pregnancy, and clinical approaches"--Provided by publisher.